LA FAMILIA PAPILIONIDAE EN CHILE (LEPIDOPTERA) (Acta Entomológica Chilena, 2022)
The only known species of Papilionidae from Chile, Battus arcliidamas (Boisduval, 1836), isredescribed in this paper. Its distribution in the country and genitalia of both sexes is discussed, aswell as its sexual dimorphism, biology and development, host plant (Aristolochia), synonymy, etc.An exhaustive discussion of the published lilerature is also presenled. The ñame Papilio psittaciisMolina 1782, can nol at all be applied to this species, and the Molina ñame ought to be invalidatedand declared unrecognizable, since there not exist type (s) of the Molina species and the originaldescription does not permit lo recognize the species.